LUMBOSACRAL AGENESIS SYNDROME IN A BABY BORN TO DIABETIC MOTHER - Alam, Malik Mahmood (Journal of Ayub Medical College Abbottabad, 2015)
This newborn was delivered full term normal vaginal delivery to a mother who had uncontrolled Diabetes. Baby had bilateral hypotonia in lower limbs and a sacral dimple. X-ray show absent vertebrae below 2nd lumber. Lumbosacrococcygeal agenesis is one of the complications of uncontrolled Maternal Diabetes. In general population the incidence of this condition is less than 0.01%.1 16% of the patients are infants of Diabetic mothers. Infants of less than 1% of diabetic mothers have this or any other osseous deformity. LSCA is graded in four types according to the severity of the condition.Type1 where only one side of the sacral agenesis is found producing hemevertebrae. Type II with complete bilateral agenesis of sacrum. Type III is total Saccrococcygeal agenesis with variable Lumber agenesis and type IV with total saccrococcygeal agenesis with variable lumber agenesis and last formed vertebrae resting on ilial bone.2,3 According to this classification our patient was having Type-III deformity. Other problems in IDM babies are hypoglycemia, Hypocalcemia, Polycythemia, cardiac malformations ,short colon syndrome. Management depends on the abnormal findings in the lower limbs and urinary symptoms. Prophylactic Antibiotics to prevent urinary Tract infections, catheterization to prevent distended bladder and laxatives for constipation may be needed. Physiotherapy for the lower limbs is important.